Revisão das espécies de Belostoma Latreille, 1807 (Insecta: Heteroptera: Belostomatidae) ocorrentes no Sudeste do Brasil - Ribeiro, José Ricardo Inácio (1999)
The species of the Neotropical genus Belostoma Latreille, 1807 from southeastem Brazil are reviewed for the first time. ln this work the following 22 species were recorded and redescribed: Belostoma anurum (Herrich-Schãffer), B. aurivi/lianum (Montandon), B. bergi (Montandon), B. bosqi De Carlo, B. candidu/um Montandon, B. costalimai De Carlo, B. cummingsi De Cario, B. da//asi De Cario, B. denta/um (Mayr), B. di/atatum (Dufour), B. discretum Montandon, B. e/ongatum Montandon, B. foveolatum (Mayr), B. horvathi Montandon, B. micantulum (Stâl), B. noua/hieri Montandon, B. oxyurum (Dufour), B. plebejum (Stâl), B. ribeiroi De Carlo, B. sanctulum Montandon, B. stollii (Amyot & Serville), and B. testaceopal/idum Latreille. Four new records from this region are reporteei: B. bergi, B. bosqi, B. dilata/um, and B. efongatum. Probably, B. minar (Palisot de Beauvois) does not occur in southeastern Brazil. The single record of this species in the region is a case of núsidentification. Six new synonynúes are established: B. candidulum Montandon, 1903 (= B. amici Piza-Jr., 1975), B. ribeiroi De Carlo, 1933 (= B. /undbladi De Carlo, 1963), B. stollii (Amyot & Serville, 1843) (= B. brasiliensis De Carlo, 1950, B. planum Lauck, 1963 and B. stolii Nieser & Melo, 1997), and B. testaceopallidum Latreille, 1807 (= B. grandico//um De Carlo, 1934). Lectotypes are designated for B. aurivillianum, B. bergi, and B. discretum. A neotype is designated for B. costa/imai. The male of B. foveolatum is described for the first time. Two distinct forms in the phallus of this species were identified Four characters have proven useful for species delinútation: the ratio between the largest width of pronotum and its length in the núddle line, the aspect of the prosternai keel, the pilosity pattem in the connexivum, and the ratio between the width of the ventral diverticulum and its length in ventral view. Lists with the morphological terms and characters suggested for these species are included, together with synonyms proposed by other taxononústs and morphologists.